(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
This article examines the practice of source usage in Abu Bakr Haddad’s work al-Jawharatu’n-nayyira based on documented evidence. The research aims to identify the sources employed by the author, classify them according to genre and madhhab affiliation, map the distribution of citations across chapters, and assess the degree to which the choice of sources influenced juristic decisions. The methodology includes content analysis grounded in textual studies, citation indexing, and chapter-based distribution (purification, prayer, commerce, marriage, criminal law, etc.). Findings indicate that the work cites over 70 sources and references more than 60 scholars; among the most frequently quoted works, al-Marghinani’s al-Hidaya stands out prominently. While maintaining the Hanafi orientation, Haddad also incorporates the views of Shafi‘i, Maliki, and other jurists, thereby reinforcing a comparative fiqh (ikhtilaf) approach in the text. The study highlights al-Jawharatu’n-nayyira’s role as an encyclopedic commentary, its intertextuality, and citation dynamics, shedding new scholarly light on the reception history of Hanafi legal theory and the tradition of commentary writing.